Embrapa's experience in the production and development of agriculture reference materials. (July 2016) - Nogueira, A R A; Souza, G B; Bossu, C M; Bianchi, S R; Verhalen, T R; Silva, P T; Peixoto, A A J; Silva, C S
Abstract: The main challenge of Embrapa is to develop a model of genuine Brazilian tropical agriculture and livestock. To get this task, the quality of laboratories results is mandatory, increasing the demand for reference materials. Projects were proposed to produce reference materials to support the national agriculture laboratories and consolidate a network able to perform reliable and reproducible analytical testing laboratory within the internationally standards required. Reference materials were produced and available to interested laboratories and collaborative tests were conducted to obtain consensus values. The results and statistical evaluations were performed with the use of software developed by Embrapa Pecuaria Sudeste.